P22 Short term imaging endpoints of flow diverter implants with and without coating for treatment of brain aneurysms: a matched pair analysis. (29th August 2022) - Kemmling, A; Schob, S; Broocks, G
Abstract : Introduction: Evidence for benefit of aneurysm treatment using coated Flow Diverter devices compared to uncoated devices is limited. Aim of study: To compare short term imaging endpoints of flow diverter implants with and without coating for treatment of saccular aneurysms in a matched pair analysis. Methods: We retrospectively included patients with incidental aneurysms who were treated with one or more flow diverters. Coated flow diverters included p64 HPC, p48 HPC, Derivo2 heal and PED2 shield. Uncoated flow diverters included p64, Derivo2 and Evolve. Coated and uncoated flow diverters were matched by location and diameters (within 20% difference) of distal and proximal landing zones and antiplatelet treatment (DAPT and SAPT). 7 patients were treated with 2 flow diverters, 7 coated and 7 uncoated. Imaging endpoints included lumen diameter, stent diameter, neointimal thickness and neointimal ratio (stent – lumen diameter)/stent diameter), rate of occlusion and MRI lesions. Peri- and postprocedural complications and clinical outcomes were evaluated. Results: 71 patients with 90 aneurysms were included. Average early follow up was 4.3 months. Periprocedural lumen diameter decreased on follow up by 27% in uncoated vs. 18% in coated devices. Neointimal thickness on follow up was 0.33 mm in coated vs. 0.45 mm in uncoated devices. Neointimal ratio was 0.32 in uncoated vs. 0.18 in coated devices. There was no difference occlusion rate, complications or clinical outcomes. Conclusions: Coated Flow Diverters showed less lumen narrowing and neointimal thickness compared to uncoated devices. This did not affect outcome and occlusion rate on short term follow up. References: Hellstern V, Aguilar Pérez M, Henkes E, Donauer E, Wendl C, Bäzner H, Ganslandt O, Henkes H. Use of a P64 MWflowdiverter with Hydrophilic Polymer Coating (HPC) and Prasugrel Single Antiplatelet Therapy for the Treatment of Unruptured Anterior Circulation Aneurysms: Safety Data and Short-term Occlusion Rates. Cardiovasc Intervent Radiol 2022 May 13. DOI: 10.1007/S00270-022-03153-8. Online Ahead of Print.Pmid:35562486 Aronov M, Pokatilov A, Luchkin V. Failure Offlowdiverter endothelization Visualized with Optic Coherent Tomography Technology. World Neurosurg 2022 May 6:S1878–8750 (22)00584–8. DOI: 10.1016/J.Wneu.2022.04.131. Online Ahead of Print. PMID:35533948 Do you have any conflict of interest to declare? : No